PENGEMBANGAN TEKNOLOGI AUGMENTED REALITY UNTUK MEDIA PEMASARAN FURNITURE MURIA JAYA BERBASIS ANDROID - Agung Kharisma Hidayah; Muhammad Husni Rifqo; Dandi Sunardi; Rahmad Aminudin (Jurnal Media Infotama, 2024)
Currently, many shops or furniture companies in Bengkulu, in terms of promoting their products to consumers and buyers, still use conventional methods, starting from offering products directly or using 2D image catalogues, one of which is Muria Jaya. Muria Jaya already has an augmented reality application for its marketing media, but the application only displays 3D models, zooms in and out on products, rotates products without any information about the product. From the augmented reality application that already exists at Muria Jaya, the application will be developed by adding voice explanations for a product, changing the color of the product in the application which makes the product more lively and attractive. This makes it easier for buyers to see the product and also determine the color when making a decision to buy a product.